Practical guidance for the use of cyclosporine ophthalmic solutions in the management of dry eye disease - de Oliveira RC (Dove Medical Press, 2019)
Rodrigo Carlos de Oliveira, Steven E WilsonCole Eye Institute, Cleveland Clinic, Cleveland, OH, USAAbstract: Dry eye disease (DED) is a multifactorial disease of ocular surface and tear film, and is a common disorder treated by eye care providers. It is well established that ocular surface inflammation has an important role in the pathophysiology of DED and that anti-inflammatory cyclosporine A (CsA) improves the treatment outcomes of most patients with DED. The purpose of this review is to provide guidance for practitioners in the use of topical CsA for the management of DED to improve patient satisfaction and the quality of life.Keywords: keratoconjunctivitis sicca, dry eye disease, cyclosporine A